Phenomenological study of elementary students' perceptions of guidance and counseling teachers' roles in developing social well-being - Setiana Setiana; Windi Asih (Jurnal Konseling dan Pendidikan, 2025)
This study aims to analyze the contribution of Guidance and Counseling (GC) services to the psychological and social well-being of elementary school students, encompassing emotional aspects, the quality of social relationships, and adaptability. The study employed a quantitative approach with a descriptive correlational design. The sample consisted of 120 students in grades IV-VI across three public elementary schools in Bandung, selected using a cluster random sampling technique. Research instruments included the Student Psychological Well-Being Scale and the Perception of GC Services Scale, which were previously validated. Data were analyzed using Pearson Product-Moment correlation. The research results demonstrated a significant positive relationship between the quality of GC services and the level of students' psychological well-being (r = 0.401; p < 0.01). Based on Guilford's criteria, this value is classified as a moderate correlation, indicating that GC services play an important role although other external factors also have an influence. These findings indicate that the optimal implementation of GC services can strengthen students' abilities in managing emotions and building healthy social relationships. This research is expected to serve as a reference for educational practitioners to reinforce the strategic role of Guidance and Counseling at the elementary school level.